Phenotypic, molecular and antimicrobial susceptibility assessment in isolates from chronic ulcers of cured leprosy patients: a case study in Southern Brazil - Luciane Cristina Gelatti; Renan Rangel Bonamigo; Ana Paula Becker; Letícia Maria Eidt; Letícia Ganassini; Pedro Alves d' Azevedo (Anais Brasileiros de Dermatologia, 2014)
BACKGROUND:One of the most stigmatizing physical sequelaeof leprosy in cured patients is the development of chronic lower extremity ulcers. The bacterial diversity present in ulcers is considered one of the factors that can delay the healing process, as well as serve as a focus for severe secondary infections.OBJECTIVE:To identify the microbiota and antimicrobial resistance profile of bacteria isolated from skin ulcers in patients cured of leprosy.METHODS:After obtaining informed consent, material was collected from ulcers of 16 patients treated at the Outpatient Public Health Dermatology Clinic of Rio Grande do Sul and Hospital Colônia Itapuã. Sampleswere collected during dressing, and the material sent to the Microbiology Laboratory of the Federal University of Health Sciences of Porto Alegre for microbiological culture. Methicillin-resistant Staphylococcus aureus(MRSA) was characterized by two molecular methods, including detection of the mecA gene by PCR and SCCmecgene typing.RESULTS:Cultures revealed microorganisms in all ulcers: Gram-negative bacilli in 80%, Gram-positive cocci in 63%, and mixed microflora in 36%. Staphylococcus aureusand Pseudomonas aeruginosa were the most prevalent bacteria. Assessment of the antimicrobial resistance profile was notable for the presence of MRSA. Molecular analysis of this isolate revealed presence of the mecA gene contained in a type IV staphylococcal cassette chromosome mec (SCCmec).CONCLUSIONS:In patients with leprosy, laboratory culture of skin ulcers is essential for correct antibiotic selection and to control emerging pathogens, such as MRSA carrying SCCmec type IV.